Tunable dispersion and dispersion slope compensator using strain-chirped fiber Bragg grating - Lee, Young Jun; Bae, Junkye; Lee, Kwanil; Jeong, Je-Myung; Lee, Sang Bae (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
We propose a tunable dispersion and dispersion slope compensator based on induced strain-chirp in a uniform fiber Bragg grating. A specially designed mechanical rotator concatenated with a metal beam with linear thickness variation along its height was used to induce a quadratic strain gradient along the grating. We successfully demonstrated the dispersion and dispersion slope change by adjusting the rotation angle and feasibility of dispersion and dispersion slope compensation at 160-Gb/s nonreturn-to-zero transmission by simulation.